Changing Trends of Climate of Doon Valley - Rawat, Laxmi (Indian Forester, 2006)
Dehra Dun (Doon Valley), the capital of Uttaranchal has been experiencing tremendous changes in its climate since last many decades. The population and number of vehicles in the valley have been increasing day by day, ultimately causing changes in its weather and climate patterns. The effect of changing climate has direct impacts on its atmospheric conditions and water resources. This article deals with changes in temperature and rainfall patterns in Doon Valley during last seventy two years (1931-2002). The variability in decadal temperature has been the highest during 1991-2000, although there is no difference in average temperature during last 3 decades. Rainfall during last 72 years has shown swinging pattern till 1979, but the rainfall has been below normal (2015.9 mm) in continuous 5 years during eighties and continuous 6 years during nineties. 1991 has received the lowest rainfall (1288.1mm) in 72 years. The article also reports increase in population in the valley in last 60 years and vehicular concentration on Dehra Dun - Delhi highway.